Continuum of violations of health for children in the region of NPP AREA - Likhoded V.S; Klopov R.V; Likhoded Y.V (Kharkov National Pedagogical University, 2010)
Information is presented about violations of health for children 7-14 years. A health level, structure of morbidity, death rate, is analysed. Perspective directions are certain to correction-prophylactic works. A safe individual health level for children to beginning of genesial and able to work period (15 years) can be formed only in solitary instances. Timely prophylactic and medical measures allow to stop the cascade of prenosological and pathological changes, provide a return to initial potential of individual health.